2007
DOI: 10.1111/j.1524-4725.2007.33220.x
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin A Adjunctive Use in Manual Chemabrasion: Controlled Long-Term Study for Treatment of Upper Perioral Vertical Wrinkles

Abstract: Previous injections of BoNTA improve short- and long-term results of chemabrasion in the upper lip region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 25 publications
1
22
0
1
Order By: Relevance
“…The longer duration of effect for static wrinkles seen in this analysis may be the result of skin remodeling. In support of this hypothesis, results from some studies have suggested that adjunctive onabotulinumtoxinA therapy improves the results of laser resurfacing, full‐face broadband light treatments, and manual chemabrasion beyond the results seen with either procedure alone . Such findings may be attributable to the ability of onabotulinumtoxinA to minimize recurrent muscle activity that has been reported to be disruptive to the lamellar organization of recently rejuvenated skin .…”
Section: Discussionmentioning
confidence: 93%
“…The longer duration of effect for static wrinkles seen in this analysis may be the result of skin remodeling. In support of this hypothesis, results from some studies have suggested that adjunctive onabotulinumtoxinA therapy improves the results of laser resurfacing, full‐face broadband light treatments, and manual chemabrasion beyond the results seen with either procedure alone . Such findings may be attributable to the ability of onabotulinumtoxinA to minimize recurrent muscle activity that has been reported to be disruptive to the lamellar organization of recently rejuvenated skin .…”
Section: Discussionmentioning
confidence: 93%
“…15 Similarly, the adjunctive use of BoNT-A has been reported to enhance the clinical improvement attained with intense pulsed light, 16,17 collagen and hyaluronic acid fillers, 11,18 and chemabrasion (trichloroacetic acid followed by dermasanding). 19 Other treatments reported to have been used in combination with BoNT-A include chemical peels 20 and fractional resurfacing. 21 One strength of this study was the number of evaluations regarding the patients' own perceptions; the patients are the ultimate judge of the success of any cosmetic treatment, and so their perceptions are one of the most important outcome end points.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in transepidermal water loss (TEWL), mechanical damping, and tactile acuity were clearly linked to age whereas lip darkness was due to hormones. Lip capacitance was unaffected by age or hormonal status 21 …”
Section: Particular Physical Signs Of Aging In Women Over 65mentioning
confidence: 94%